Pengaruh Kebijakan Dividen Dan Profitabilitas Terhadap Harga Saham Emiten LQ 45 Tahun 2009-2018 - Narayanti, Ni Putu Laksmi; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 30 No 2 (2020)DO - 10.24843/EJA.2020.v30.i02.p19, 2020)
This study aims to obtain empirical evidence of the relationship between dividend policy and profitability on the o stock prices. The population in this study are companies registered in the LQ-45 period 2009 - 2018, the reason issuers contained in this index tend to distribute dividends and have high trade liquidity. The sampling technique in this study was purposive sampling and the total observation companies were 6 sample companies. Data analysis techniques using Multiple Linear Regression Analysis. As the results, the devidend policy brings a possitive effect on the stock prices, and the profitability that has been proxied by ROA also brings a possitive effect on the company’s stock price. Keywords: Devidend Policy; Stock Prices; Profitability; LQ45.